(untitled) (Práxis Educativa, 2017)
This paper investigates how the condition of queer critique not only reflects in the sphere of social exchange, but it can acquire methodological dimensions to the extent that allows reapply to the investigative positions and the paths of curriculum research ironic and jocular style redefinition of the queer insult. The explored argument is that the queer critique allows to question the normative naturalization of research procedures into the curriculum as those contained in the formulas that tend to oppose researcher/researched, realism/fiction, coherence/multiplicity. From the perspective of taking queer as a heterogeneous reading, this text explores how four notes, combinations, wanderings, affectations and fertilizations, translate what happens when queering research methodology. Movements that can be seen as wandering experiments in relation to the paradigm of queer critique in Education and curriculum. Keywords: Queer methodology. Localization. Curriculum research.